Understanding workplace collaboration in professional rugby coaching: a dramaturgical analysis - Hall, E. T.; Nichol, A. J.; Morgan, C. T.; McCutcheon, M.; Potrac, P. (Qualitative Research in Sport, Exercise and Health, 2024)
This ethnography examined the occupational teamwork of a Head Coach and his colleagues (assistants) in the rarely accessed world of professional rugby union. Extensive field notes and participant interviews were subject to emic and etic interpretations. The heuristic framework comprised the work of both classic and contemporary dramaturgical theorists. Our analysis generated novel findings regarding the everyday strategies and tactics that underpinned the collaborative production of this team`s workplace performances. These included how a team identity was constructed and how the Head Coach pursued co-operation, envisioned and advocated for collective missions, and sustained team ventures in their rhythmical doing of organisational life. This study is among the first to provide situated insights into how team performance was productively managed, negotiated, and co-ordinated in the context of a high-performance sport workplace. The insights provided hold significance for researchers, practitioners, educators, and other stakeholders concerned with the dramaturgical demands of organisational life, and with the coherent doing of sports work by managers (head coaches) and their colleagues.